Genetic Grouping Algorithm based on Rank and Research Group for Timetabling Thesis Examination - Habibie Ed Dien; M. Hasyim Ratsanjani; Andhika Satrio Wiratama; Vit Zuraida (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2023)
Timetabling is a common problem faced by various academic institutions, especially in the process of timetabling thesis examination. In the process of timetabling thesis examination there are several problems that arise, namely the problem of determining examiners and their order, arranging space and time slots, which makes the timetabling process inefficient. This problem will be solved by using a genetic grouping algorithm (GGA) combined with the parameters of rank and research groups (RG), which have proven to be efficient to use to solve problems such as in the thesis exam timetabling process. The results showed that GGA with ran and RG succeeded in increasing efficiency by 99,97% when applied to solving this problem in the thesis exam timetabling process.